Factors Influencing Poverty Among Shrimp Farming in East Java: Poverty Among Shrimp Farmers - Gimnastiar, Muhammad Akbar; Andriatmoko, Novil Dedy (Agriculture Socio-Economic Department, Faculty of Agriculture, Brawijaya University, 2025)
Background and purpose – Poverty among shrimp farming households remains a significant challenge despite the sector’s potential to generate substantial income and contribute to rural economic growth. In regions such as Bangil District, Pasuruan Regency, East Java, many shrimp farmers face persistent poverty due to constraints related to household demographics, limited resources, and restricted access to services. This study aims to identify and quantify the factors influencing the likelihood of shrimp farmers being above or below the poverty line, providing empirical evidence to inform targeted poverty reduction strategies in the aquaculture sector. Methodology – Primary data were collected from 78 randomly selected shrimp farmers in Bangil District through structured interviews, observations, and documentation during October–November 2024. The study employed a probit regression model to analyze the effect of ten explanatory variables—cultivation experience, household size, education level, land area, age, number of working household members, land ownership, access to healthcare, access to information, and farmer group participation—on poverty status. Findings – The results indicate that five variables significantly influence poverty status: number of family members, length of formal education, land area, number of working family members, and land ownership. Larger households are associated with a higher likelihood of poverty, while greater education, larger pond size, more working members, and secure land ownership reduce poverty risk. Conversely, cultivation experience, age, access to healthcare, access to information, and farmer group participation show no statistically significant effect. Implications – The findings suggest that policies aiming to reduce poverty among shrimp farmers should focus on improving education and technical training, ensuring secure and equitable land access, promoting off-farm income opportunities, and strengthening household labor capacity. Integrated strategies involving credit access, infrastructure development, and market linkages are essential to enhance resilience and raise household welfare in shrimp farming communities.